2008
DOI: 10.1029/2007wr006366
|View full text |Cite
|
Sign up to set email alerts
|

A vertical dispersion model for solute exchange induced by underflow and periodic hyporheic flow in a stream gravel bed

Abstract: [1] Interstitial flows in stream gravel beds are driven by stream slope and controlled by hydraulic conductivity (underflows) or induced by pressure differentials on the streambed surface (hyporheic flows). They enhance solute exchange between surface water and a streambed. To study the solute transport in a stream gravel bed, a 2-D transient advectiondispersion mass transfer model was formulated. The velocity field includes an underflow and a spatially periodic hyporheic flow, e.g., due to standing surface wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 44 publications
0
68
0
Order By: Relevance
“…Groundwater (fresh or saline, any flow process) Groundwater (regional flow of fresh or saline groundwater) interface Qian et al, 2008). Other studies have shown that a corresponding exponential decay in D eff reproduces field (Jahnke et al, 2005) and laboratory (Qian et al, 2009) observations, using…”
Section: Hydrologymentioning
confidence: 87%
“…Groundwater (fresh or saline, any flow process) Groundwater (regional flow of fresh or saline groundwater) interface Qian et al, 2008). Other studies have shown that a corresponding exponential decay in D eff reproduces field (Jahnke et al, 2005) and laboratory (Qian et al, 2009) observations, using…”
Section: Hydrologymentioning
confidence: 87%
“…move from high to low concentration areas even when no net exchange of water occurs. Similarly, hyporheic exchange can be viewed as a dispersive process in the riverbed, with no net exchange of water but a transport of solutes from high to low concentration areas (Qian et al, 2008). In applying the concept developed for estuaries to hyporheic exchange, the discharging groundwater flowing through the hyporheic zone is considered to act as 25 the 'river', the hyporheic zone is considered to act as the 'estuary', and surface water is considered to act as the 'ocean' end-member.…”
Section: Site Descriptionmentioning
confidence: 99%
“…The effective dispersion coefficient decays exponentially with depth below the sediment-water interface (Elliott and Brooks 1997;Jahnke et al 2005;Qian et al 2008Qian et al , 2009), so that…”
Section: Modeling Of Porewater Temperaturesmentioning
confidence: 99%